Enhanced hydrogen generation behaviors and hydrolysis thermodynamics of as-cast Mg–Ni–Ce magnesium-rich alloys in simulate seawater. (13th September 2019) - Hou, Xiaojiang; Wang, Yi; Yang, Yanling; Hu, Rui; Yang, Guang; Feng, Lei; Suo, Guoquan; Ye, Xiaohui; Zhang, Li; Shi, Hongchang; Yang, Lu; Chen, Zhi-Gang
Abstract: In this study, we developed as-cast (Mg10Ni)1- x Ce x ( x  = 0, 5, 10, 15 wt%) ternary alloys by using a flux protection melting method and investigated their hydrolysis hydrogen generation behaviour in simulate seawater. The phase compositions and microstructures of as-cast (Mg10Ni)1- x Ce x ternary alloys are characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) equipped with electron energy dispersion spectrum (EDS) and transition electron microscope (TEM). Their kinetics, thermodynamics, rate-limiting steps and apparent activation energies are investigated by fitting the hydrogen generation curves at different temperatures. With increasing Ce content, the (Mg10Ni)1- x Ce x ternary alloys show increased electrochemical activities and decreased eutectic. When 10 wt% and 15 wt% Ce added, the active intermediate phase of Mg12 Ce has been observed. The hydrogen generation capacity of (Mg10Ni)95 Ce5 is as high as 887 mLg −1 with a hydrolysis conversion yield of 92%, which is higher than that of Mg10 Ni alloys (678 mLg −1 ) with a yield only 75% at 291 K. The initial hydrolysis reaction kinetics of Mg–Ni–Ce alloys is mainly controlled by the electrochemical activity and the mass transfer channels formed in the alloys. Such a structure-property relationship will provide a possible strategy to prepare Mg-based alloys with high hydrogen conversion yield and controlled hydrolysis kinetics/thermodynamics. Graphical abstract: Image 1 Highlights: Ce promotes self-activity and more multiphase microstructure of Mg–Ni–Ce alloys. Increased temperature and Ce can improve initial H2 production rate and capacity. The capacity of (Mg10Ni)95 Ce5 alloy is 887 mLg −1 at 291 K in simulate seawater. Hydrolysis H2 generation mechanism of Mg–Ni–Ce alloys is proposed.